Анатомічна характеристика листка деяких видів роду Lonicera L., які культивуються на південному березі Криму - Brailko, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The anatomical structure of the leaf plates of 9 species and 2 garden forms of honeysuckle growing in the conditions of the Southern coast of Crimea has been described. Their structural features in relation to environmental adaptability have been studied. Species Lonicera tatarica, L. etrusca, L. fragrantissima, L. japonica and L. nitida ‘Elegant’, have been identified as those are differ with the presence of xeromorphic signs complex and to a certain extent can be adapted to arid conditions and grown in a limited irrigation.